Identification of methylenecyclopropyl acetic acid in serum of European horses with atypical myopathy. (3rd September 2013) - Votion, D.‐M.; van, G.; Sweetman, L.; Boemer, F.; de, P.; Dopagne, C.; Lefère, L.; Mouithys‐Mickalad, A.; Patarin, F.; Rouxhet, S.; van, G.; Serteyn, D.; et al.
Summary Reasons for performing study It is hypothesised that European atypical myopathy (AM) has a similar basis as seasonal pasture myopathy in North America, which is now known to be caused by ingestion of hypoglycin A contained in seeds from the tree Acer negundo. Serum from horses with seasonal pasture myopathy contained the conjugated toxic metabolite of hypoglycin A, methylenecyclopropyl acetic acid (MCPA). Study design Retrospective study on archived samples. Objectives 1) To determine whether MCPA‐carnitine was present in serum of European horses confirmed to have AM; 2) to determine whether Acer negundo or related Acer species were present on AM pastures in Europe. Methods Concentrations of MCPA‐carnitine were analysed in banked serum samples of 17 AM horses from Europe and 3 diseased controls (tetanus, neoplasia and exertional rhabdomyolysis) using tandem mass spectrometry. Atypical myopathy was diagnosed by characteristic serum acylcarnitine profiles. Pastures of 12 AM farms were visited by experienced botanists and plant species were documented. Results Methylenecyclopropyl acetic acid‐carnitine at high concentrations (20.39 ± 17.24 nmol/l; range 0.95–57.63 nmol/l; reference: <0.01 nmol/l) was identified in serum of AM but not disease controls (0.00 ± 0.00 nmol/l). Acer pseudoplatanus but not Acer negundo was present on all AM farms. Conclusions Atypical myopathy in Europe, like seasonal pasture myopathy in North America, is highly associated with the toxic metabolite of hypoglycin A, MCPA‐carnitine. This finding coupled with the presence of a tree of which seeds are known to also contain hypoglycin A indicates that ingestion of Acer pseudoplatanus is the probable cause of AM. This finding has major implications for the prevention of AM.